ALIH KODE DALAM VIDEO BLOG KANAL YOUTUBE “NIHONGO MANTAPPU” - Putri, Widyawati Hema Mona; Andriyani, Anak Agung Ayu Dian (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
This study aims to determine code switching in the form of language switching and the factors behind the occurrence of code switching that occurs in the interaction of students from Indonesia with students from Japan. The results of the study show that in interactions with video blogs on the YouTube channel "Nihongo Mantappu" there is often a change of language when communicating. In this study, one form of code switching was found, namely code switching in the form of language switching. In addition, there are factors that cause code-switching such as mastery of more than one language, balancing the language skills of the interlocutor, factors in the process of learning other languages, factors of lack of mastery of languages and habitual factors. The habit factor in question is that the insertion of language is done subconsciously or reflexively, this is influenced by the habit of switching from Indonesian to Japanese or Japanese to Indonesian.